Mediating Role of Meaningful Work between Sustainable Human Resource Management and Employee Engagement: A study on banking sector of Pakistan - Shaista Nasir; Ajmal Waheed (Al-Qanṭara, 2022)
Abstract Organizations today take sustainability stance and its related elements as the key objective in order to become the agent of sustainable development. Research studies on organizational sustainability is increasing with the passage of time. The objective of the current study was not just to discuss the significance of sustainable HRM in banking industry but the objectives were to find out the role of sustainable HRM in creating employee engagement. In relation with studying the association between sustainable HRM and employee engagement, this study also proposed and studied meaningful work as a mediator between the positive relationship of sustainable HRM and employee engagement. This study used quantitative research design. Structured questionnaire was used for the collection of data from 250 employees working in the commercial banks of Islamabad and Rawalpindi through convenient sampling technique. SPSS (Statistical Package for Social Sciences) version-28 is used for descriptive analysis while proposed hypotheses were tested through PLS-SEM (Partial Least Square Structural Equation Modeling) version 3.2. The study results showed positive correlation between sustainable HRM and employee engagement. Similarly, it has been found that meaningful work partially mediates the relationship of sustainable HRM with employee engagement. Practical implications of the result were also discussed.